Pemahaman virtual metode IMRAD bagi mahasiswa Fakultas Hukum Universitas Borneo Tarakan - Tomy Michael (Yumary: Jurnal Pengabdian kepada Masyarakat, 2020)
Purpose: To introduce the AKB method journal to students of the Faculty of Law, University of Borneo Tarakan. Methods: This community service activity was divided into several stages: the planning and implementation stages. It also used questions and answers. Results: As students still use old techniques that are based on background, problem formulation, research, and suggestions, therefore this technique is beneficial for students to conduct better research in the future. Conclusion: The IMRAD method must be mandatory in producing universal legal research since students' abilities have improved with the IMRAD method. Keywords: IMRAD, Training, Journal